Synthesis, characterization, and electrochemical and electrical properties of novel mononuclear and binuclear ball-type Zn(II) and Co(II) phthalocyanines substituted with 1a,8b-dihydronaphtho[b]naphthofuro-[3,2-d]furan-7,10-diyl - Bekaroglu, Oezer; Bulut, Mustafa; Salih, Bekir; Odabas, Zafer; Altindal, Ahmet; Oezkaya, Ali Riza (Elsevier BV, 2007)
Abstract New mononuclear phthalocyanines [Zn(II) 4 and Co(II) 6] and ball-type bisphthalocyanines [Zn(II) 5 and Co(II) 7] have been synthesized from the corresponding compound 3, which can be obtained from the reaction of 4-nitrophthalonitrile 1 with 1a,8b-dihydronaphtho[b]naphthofuro[3,2-d]furan-7,10-diol 2. The novel compounds have been characterized by elemental analysis, UV/Vis, IR, 1H NMR and MASS spectroscopy. The electrochemical measurements show the formation of various mixed-valence oxidized and reduced species, due to intramolecular interactions between the two phthalocyanine units in the ball-type binuclear metallophthalocyanines. Detailed studies of the effect of temperature on the electronic properties of the films were investigated by dc conductivity and impedance spectroscopy techniques at temperatures between 290 K and 460 K. Thermally activated conductivity dependence on temperature was observed from the dc measurements. The ac results give a power law behavior in which the frequency exponent decreases with temperature. It was observed that the impedance spectra consist of a curved line at low temperature. These curved lines transform into a full semicircle with increasing temperature.